Somatic and mental health of and the COVID-19 pandemic’s impact on adolescents diagnosed with asthma - Maria Emilsson; Kourosh Bador; Catrin Johansson; Nóra Kerekes (npj Primary Care Respiratory Medicine)
Abstract Adolescents with asthma are at heightened risk of somatic and mental health challenges, particularly during large-scale stressors such as the COVID-19 pandemic. This study explored the self-reported prevalence of asthma, co-occurring somatic complaints, psychological distress, and perceived pandemic impact in a multinational sample of 4802 upper secondary school students (aged 15–19) from Sweden, the United States, Serbia, Morocco, and Vietnam. Participants completed a web-based survey between November 2020 and June 2021. Approximately 9% reported having a physician-diagnosed asthma condition, with prevalence varying across countries. An additional 3.2% of the total sample reported uncertainty about whether they had asthma, with this uncertainty most frequently observed in Vietnam and Morocco. Adolescents with asthma reported slightly higher psychological distress than their peers without asthma, particularly among females, yet paradoxically reported a lower perceived impact of the pandemic on daily life. Physical activity levels were comparable between groups. Asthma was found to be associated with several co-occurring somatic complaints, with one gender-specific pattern observed in relation to thyroid disease. The observed variability in asthma prevalence and diagnostic uncertainty underscores the influence of national healthcare systems, health literacy, and communication practices. These findings highlight the need for gender-sensitive and context-aware approaches in adolescent health care, especially during global public health disruptions.